2001
DOI: 10.1093/jn/131.7.1973
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Feeding Enhances Glycogen Repletion in Liver and Skeletal Muscle of Rats

Abstract: To investigate the efficacy of the ingestion of vinegar in aiding recovery from fatigue, we examined the effect of dietary acetic acid, the main component of vinegar, on glycogen repletion in rats. Rats were allowed access to a commercial diet twice daily for 6 d. After 15 h of food deprivation, they were either killed immediately or given 2 g of a diet containing 0 (control), 0.1, 0.2 or 0.4 g acetic acid/100 g diet for 2 h. The 0.2 g acetic acid group had significantly greater liver and gastrocnemius muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 41 publications
5
118
0
3
Order By: Relevance
“…Liljeberg and Björck (1998) reported that vinegar significantly reduced the postprandial glucose and insulin responses to a starchy meal in healthy subjects and suggested that the mechanism was related to delayed gastric emptying as judged from lower paracetamol levels after the test meal with vinegar. Conversely, in rats fed experimental diets containing the indigestible marker polyethyleneglycol and various concentrations of acetic acid, dietary acetic acid did not alter gastric emptying, food intake, or glucose absorption (Fushimi et al 2001). Thus, the effect of vine- Four patients (patients 1 to 4) showed improvement of their menstrual cycle and are indicated by unbroken lines, while three (patients 5 to 7) without improvement are shown by dotted lines.…”
Section: Discussionmentioning
confidence: 90%
“…Liljeberg and Björck (1998) reported that vinegar significantly reduced the postprandial glucose and insulin responses to a starchy meal in healthy subjects and suggested that the mechanism was related to delayed gastric emptying as judged from lower paracetamol levels after the test meal with vinegar. Conversely, in rats fed experimental diets containing the indigestible marker polyethyleneglycol and various concentrations of acetic acid, dietary acetic acid did not alter gastric emptying, food intake, or glucose absorption (Fushimi et al 2001). Thus, the effect of vine- Four patients (patients 1 to 4) showed improvement of their menstrual cycle and are indicated by unbroken lines, while three (patients 5 to 7) without improvement are shown by dotted lines.…”
Section: Discussionmentioning
confidence: 90%
“…Acetic acid has various kinds of biological activities, [19][20][21] but at high concentrations, solutions of acetic acid are difficult to drink because of a strong sour taste. In this study, we tried to improve the sourness of acetic acid by glucosylation, and we remarkably reduced its sour taste by glucosylation of its carboxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed to evaluate the potential effects of acetic acid on glucose metabolism. Acetic acid has thus been shown to suppress disaccharidase activity in Caco-2 cells (human colonic carcinoma cells) (Ogawa et al, 2000) and to activate gluconeogenesis and induce glycogenesis in the rat liver after a fasting state (Fushimi et al, 2001). Although it has been established that the presence of acetic acid in a meal delays the gastric emptying rate and thus reduce postprandial glycaemia (Ebihara & Nakajima, 1988;Liljeberg & Björck, 1998), more studies are needed to elucidate to what extent other physiological mechanisms also may be involved and affect glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%